2021
DOI: 10.1002/jmv.26738
|View full text |Cite
|
Sign up to set email alerts
|

Controversy over smoking in COVID‐19—A real world experience in New York city

Abstract: Data are conflicting regarding the impact of tobacco smoking in people with pneumonia due to SARS-CoV-2 infection . We performed a retrospective multicentre cohort study of 9991 consecutive patients hospitalized in a major New York academic center between March 7th and June 5th, 2020 with laboratory-confirmed COVID-19. The clinical outcomes assessed included risk of hospitalization, in-hospital mortality, risk of intensive care unit (ICU) admission, and need for mechanical ventilation among smokers (current an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
4
8
0
Order By: Relevance
“…Except this low percentage, we found that tobacco smoking was statistically significant associated with decreased risk of ICU admission. Our results find support to Julia Hippisley-Cox study [50] and all previous reposted studies [46][47][48].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Except this low percentage, we found that tobacco smoking was statistically significant associated with decreased risk of ICU admission. Our results find support to Julia Hippisley-Cox study [50] and all previous reposted studies [46][47][48].…”
Section: Discussionsupporting
confidence: 90%
“…However, this assertion is much more an expectation rather than real-world data [45]. A China study found that the smoking prevalence among COVID-19 patients was 10.2%, [46], following the low prevalence of current smokers among hospitalized COVID-19 that is a common finding across several countries [46][47][48][49].…”
Section: Discussionmentioning
confidence: 99%
“…Even with an initial pool of 100 smokers, some studies only observed 2 or 3 deaths within that group, making statistical analysis difficult. Some of the studies that did not find a significant association in multivariable analysis found increased mortality risk in univariate analysis [ 18 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Purkayastha and colleagues, through modeling the direct effects of cigarette smoke on SARS-CoV-2 infection, showed that acute cigarette smoke exposure increases the number of infected and apoptotic cells, prevents the normal airway basal stem cell repair response, suggesting that smoke increases COVID-19 severity 39 . However, it has been shown that smoking was not associated with increased mortality in COVID-19 pneumonia 40,41 , but cumulative smoking exposure, as measured by pack/years, was associated with a higher risk of hospitalization and mortality from COVID-19 in a dose-dependent manner 42 . In contrast, cigarette smoke-pretreatment potently abrogates SARS-CoV-2 replication in an vitro model 34 .…”
Section: Discussionmentioning
confidence: 99%